2010
DOI: 10.1002/lary.21650
|View full text |Cite
|
Sign up to set email alerts
|

PET‐CT Staging of the Neck in Cancers of the Oropharynx: Patterns of Regional and Retropharyngeal Nodal Metastasis

Abstract: Objective: To study the retropharyngeal lymph node status (RPLN) by pretreatment PET-CT imaging in patients with squamous cell carcinomas of the oropharynx (OPSCC). Study Design: Retrospective.Methods: 101 patients with a biopsy proven OPSCC were identified. 53 patients meeting inclusion criteria were further analyzed. Conclusions: Pre-treatment PET-CT can be used as a staging tool to aid in treatment planning of OPSCC, as rates of RPLN and nodal metastasis are consistent with those reported in the literature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
1
17
1
Order By: Relevance
“…Tang et al 5 studied a cohort of 165 patients with OPC, 134 of whom had HPV-associated disease, and observed a 12% incidence of RPLN involvement, similar to the 9% incidence observed in the current study cohort and the 10% incidence observed in our 2013 study, although lower than the incidence of 16% to 21% reported by others. 3,[14][15][16] The discrepancy in the RPLN incidences reported in these study populations compared with that in the current study may be related to differences in the percentage of patients with locally advanced OPC in each study cohort. For example, the percentage of patients with T3-T4 disease in the referenced studies ranged from 46% to 64%, which is higher than the rate of 42% observed in the study by Tang et al 5 and the rate of 28% (224 of 796 patients) observed in the current study.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Tang et al 5 studied a cohort of 165 patients with OPC, 134 of whom had HPV-associated disease, and observed a 12% incidence of RPLN involvement, similar to the 9% incidence observed in the current study cohort and the 10% incidence observed in our 2013 study, although lower than the incidence of 16% to 21% reported by others. 3,[14][15][16] The discrepancy in the RPLN incidences reported in these study populations compared with that in the current study may be related to differences in the percentage of patients with locally advanced OPC in each study cohort. For example, the percentage of patients with T3-T4 disease in the referenced studies ranged from 46% to 64%, which is higher than the rate of 42% observed in the study by Tang et al 5 and the rate of 28% (224 of 796 patients) observed in the current study.…”
Section: Discussioncontrasting
confidence: 73%
“…However, within the context of other variables, the potential relationship between RPLN and outcomes may be difficult to demonstrate. Tang et al studied a cohort of 165 patients with OPC, 134 of whom had HPV‐associated disease, and observed a 12% incidence of RPLN involvement, similar to the 9% incidence observed in the current study cohort and the 10% incidence observed in our 2013 study, although lower than the incidence of 16% to 21% reported by others . The discrepancy in the RPLN incidences reported in these study populations compared with that in the current study may be related to differences in the percentage of patients with locally advanced OPC in each study cohort.…”
Section: Discussionsupporting
confidence: 65%
“…Despite the RPLN group being described as a nodal bed at risk for spread from oropharyngeal cancer (OPC), there are only a few reports in the medical literature that have documented the incidence of RPLN involvement in OPC, and among these, the impact of RPLN involvement on oncologic outcomes has been ambiguous . Because clinical RPLN involvement from OPC is a reportedly infrequent occurrence, and because RPLNs are neither readily amenable to direct clinical examination nor included in routine neck dissections, a large modern cohort of OPC patients with long‐term follow‐up initially staged with advanced imaging modalities inclusive of the skull base is necessary to accurately estimate both the incidence of clinical/radiographic RPLN involvement and subsequent impact on clinically relevant oncologic outcomes with sufficient power.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical management of the neck in patients with pharyngeal cancers does not usually involve a dissection of the retropharyngeal lymph node (RPLNs). Neck dissections do not routinely address RPLNs, creating a potential for recurrence in the retropharynx and the need to address this nodal basin with radiotherapy (Tauzin, et al, 2010). Treatment of the neck in patients with clinical evidence of nodal metastasis has traditionally been surgical.…”
Section: General Principlesmentioning
confidence: 99%